[PP.10.08] SUBCLINICAL ATHEROSCLEROSIS AND BLOOD PRESSURE LEVELS DURING 5 YEARS OF ANTI-TNFALPHA TREATMENT IN PSORIATIC ARTHRITIS PATIENTS. (September 2017) - Puato, M.; Pesavento, R.; Rattazzi, M.; Ortolan, A.; Ramonda, R.; Pauletto, P.
Abstract : Objective: The aim of this study was to evaluate the effect of 5 years of anti-TNFalpha treatment on subclinical atherosclerosis progression. Psoriatic Arthritis (PsA) is associated with accelerated atherosclerosis and increased cardiovascular mortality. Influence of anti-TNFalpha treatment of PsA in subclinical atherosclerosis is still unclear. Design and method: Twenty-seven consecutive PsA patients were evaluated before TNF blockers therapy (T0), after 2 years (T1) and after 5 years (T2) of treatment. Subclinical atherosclerosis was evaluated through carotid duplex scanning, analyzing intima-media thickness (IMT) and flow-mediated dilation (FMD). IMT values were expressed as IMT mean (cumulative mean of all the IMT mean in every analyzed carotid segment) and M-MAX (cumulative mean of all the higher IMT in every analyzed carotid segment). Response to therapy was studied by the evaluation of DAS 28 (disease activity score), and C-reactive protein (CRP). Results: A good response to treatment was evident already at T1, with a significant decrease of DAS 28 (4.16 vs 2.30, p < 0.01) and CRP (11.25 vs 2.91, p < 0.01). The efficacy was preserved from T1 to T2 in terms of DAS 28 (2.30 vs 2.40, p = ns), CRP (2.91 vs 2.73, p = ns). From T0 to T1 there was a significant increment in both IMT-mean and M-MAX (0.72 vs 0.91 and 0.89 vs 1.06, respectively, p < 0.01). At T2 IMT-mean did not change significantly (0.91 vs 0.92, p = ns), while M-MAX worsened further (1.10 vs 1.06, p < 0.05). No significant variation in FMD values was observed during the 5-year follow up (T0 5.40%, T1 5.37%, T2 5.40%, p = ns). Noteworthy, systolic blood pressure and BMI remained stable from T0 to T2 (132 vs 131 mmHg, p = ns, and BMI 26 vs 25, p = ns), while diastolic blood pressure decreased significantly (79 vs 74 mmHg, p = 0.001). Conclusions: Our data revealed that in patients with PsA, despite treatment with TNF blockers, there is still a gradual, albeit slight progression of subclinical atherosclerosis assessed by ultrasonography. Other inflammatory mechanisms not related to TNF may be responsible of the progression of the atherosclerotic disease.